Post-traumatic osteoarthritis: A review of pathogenic mechanisms and novel targets for mitigation - Julian E. Dilley; Margaret Anne Bello; Natoli Roman; Todd McKinley; Uma Sankar (Bone Reports, 2023)
Post-traumatic osteoarthritis (PTOA) develops secondary to a joint injury and accounts for 12 % of all osteoarthritis. These injuries, often of the lower extremity joints, occur due to trauma or accidents related to athletic or military activities. They primarily affect younger individuals although PTOA can occur across the spectrum of age. Pain and functional disability caused by PTOA confer a heavy economic toll on patients, in addition to detrimentally affecting their quality of life. Both high energy injuries that cause articular surface fracture with or without subchondral bone disruption and low-energy injuries involving joint dislocations or ligamentous injury cause PTOA, albeit through different mechanisms. Regardless, chondrocyte death, mitochondrial dysfunction, reactive oxygen species production, subchondral bone remodeling, inflammation and cytokine release in the cartilage and synovium play integral roles in the pathogenesis of PTOA. Evolving surgical methods are focused on stabilizing articular surface and joint structure congruity. However, to date there are no disease modifying medical therapies against PTOA. Increased recent understanding of the pathogenesis of the subchondral bone and synovial inflammation as well as that of chondrocyte mitochondrial dysfunction and apoptosis have led to the investigation of new therapeutics targeting these mechanisms to prevent or delay PTOA. This review discusses new advances in our understanding of cellular mechanisms underlying PTOA, and therapeutic approaches that are potentially effective in reducing the self-propagating cycle of subchondral bone alterations, inflammation, and cartilage degradation. Within this context, we focus therapeutic options involving anti-inflammatory and anti-apoptotic candidates that could prevent PTOA.